High-Stakes Testing & Student Learning - Audrey L. Amrein; David C. Berliner (Arizona State University, 2002)
A brief history of high-stakes testing is followed by an analysis of eighteen states with severe consequences attached to their testing programs. These 18 states were examined to see if their high-stakes testing programs were affecting student learning, the intended outcome of high-stakes testing policies promoted throughout the nation. Scores on the individual tests that states use were not analyzed for evidence of learning. Such scores are easily manipulated through test-preparation programs, narrow curricula focus, exclusion of certain students, and so forth. Student learning was measured by means of additional tests covering some of the same domain as each state's own high-stakes test. The question asked was whether transfer to these domains occurs as a function of a state's high-stakes testing program.